Synthesis of Arylethyl (E)-Styrylsulfones and Arylsulfones by One-Pot DIBAL-H/NaH-Mediated Reaction of β-Ketosulfones - Chang, Meng-Yang; Chen, Yi-Chia; Chan, Chieh-Kai (Synlett, 2014)
A facile one-pot synthetic route for preparing a series of arylethyl (E)-styrylsulfones or arylethyl arylsulfones is developed. The efficient one-pot DIBAL-H/NaH-mediated route includes reduction of α-benzyl-β-arylketosulfones and retroaldol/aldol or retroaldol reaction of the resulting intermediate. The DIBAL-H/NaH-mediated reaction mechanism has been discussed.
Keywords: aldol reaction; aluminum; condensation; sulfones; tandem reaction